Persistence of psychiatric disorders in a cohort of HIV/AIDS patients in South Africa: A 6-month follow-up study (2006)
Background: Psychiatric disorders in HIV/AIDS are common, emerging soon after diagnosis or during the subsequent course of illness. However, there are few prospective studies on the rates of psychiatric disorders in HIV/AIDS, particularly in the context of the developing world. Methods: Sixty-five patients with recently diagnosed HIV were interviewed on presentation to a hospital-based HIV clinic and then 6 months later. On both interviews, the patients were assessed using the MINI International Neuropsychiatric Interview, the Carver Brief COPE, and the Sheehan Disability Scale. Exposure to negative life events and risk behaviors was also evaluated. Results: The overall prevalence of psychiatric disorders in the follow-up period remained high (56% of patients had at least one psychiatric disorder at baseline, and 48% of patients had at least one psychiatric disorder at 6 months). Depression and posttraumatic stress disorder (PTSD) were the most prevalent disorders at both baseline (34.9% and 14.8%) and follow-up (26% and 20%), respectively. More than half of all patients with depression at baseline improved (16 of 29; 55.1%). However, there was a new onset of both depression (4 of 49; 8.1%) and PTSD (12 of 17; 70.5%) on follow-up. In univariate analysis, depression on follow-up was significantly associated with: (a) disability in work/social/family functioning, (b) greater number of negative life events, and (c) a decline in CD4 lymphocyte count. Univariate analysis also revealed that a diagnosis of PTSD on follow-up was significantly associated with (a) a longer duration of infection and (b) baseline disability in work/social/family functioning. However, in multivariate analysis, only disability scores predicted the diagnoses of major depression and PTSD on follow-up assessment. Persistence of risky sexual behaviour was also noted, with a significantly higher number of participants reporting nonuse of condom on follow-up. There appeared to be a shift from maladaptive coping behaviors to more adaptive coping behaviors over the 6-month period. Conclusion: The rate of psychiatric disorders in HIV/AIDS patients was consistent over time. These findings emphasize the importance of regular evaluation for psychiatric disorders in HIV/AIDS patients, not only at the commencement of treatment but also during subsequent follow-up visits.